GROSS FIXED CAPITA FORMATION, INTEREST RATE AND ECONOMIC GROWTH IN NIGERIA - Abraham Anthony; Chidi Wosu (Journal of Economic and Economic Policy, 2026)
Objective: This study examines the association between gross fixed capita formation, interest rate and economic growth in Nigeria from 1980-2024. Economic growth, a Proxy for gross domestic product (GDP) is used as the independent variable in the model for the study while the dependent variables are gross fixed capital formation, interest rate, maximum lending rate, prime lending rate and savings rate. Method: The techniques applied are the Ordinary Least Square of multiple regression analysis, unit root test, Co-integration test and Error Correction Mechanism techniques. Unit root results revealed that the variables are integrated of order 1(1). The study also revealed that a long run connection among the variables used exists. Results: The result of the R2 is 0.674298 indicating that the link between the dependent variable and independent variables is 67 per cent. Again, stability test confirmed that stability was found given the result of the Recursive and CUSUM tests. The error correction term indicates significant correction of about 0.748989 or 74 percent from short run disequilibrium to long run equilibrium. This 74 percent is the adjustment speed from short run disequilibrium to its long run equilibrium. Novelty: The study concludes that government should enact healthier policies as it regards to monetary policies considered effective and must also be implementable to back the interest rate hence deepening the operational efficiency of the financial market and thus enhance Nigeria gross fixed capital formation. The study recommends an enhanced gross fixed capita formation, maximum lending rate and savings rate since they have positive and significant effect on gross domestic product in Nigeria while interest rate and prime lending rate which have negative and statistically insignificant link with gross domestic product in Nigeria should be reduced.